Endometrial hyperplasia in pre-menopausal women: A systematic review of incidence, prevalence, and risk factors. (April 2022) - Petersdorf, Kathrin; Groettrup-Wolfers, Esther; Overton, Paul M.; Seitz, Christian; Schulze-Rath, Renate
Highlights: The true incidence and prevalence of endometrial hyperplasia (EH) are uncertain. Published data are heterogeneous due to variation in populations and methodology. Because diagnosis is invasive, estimating population prevalence is challenging. Here, we describe the incidence and prevalence of EH in large, published studies. We provide an overview of factors that might influence observed rate differences. Abstract: Objectives: Hormonal therapies have been associated with a range of effects on the endometrium, including endometrial hyperplasia (EH). With many medicinal products being developed for pre-menopausal women, epidemiological data regarding the population background risk could meaningfully supplement comparative risk data gathered in clinical trials. However, epidemiological studies on EH often focus on post-menopausal women. We aimed to assess the available observational evidence on the incidence and prevalence of EH among pre-menopausal women and to investigate the influence of specific risk factors. Study design: We conducted systematic literature searches on 27 August 2021, using the Embase and PubMed databases. Searches were designed to identify studies of EH epidemiology, published in English on or after 1 January 1995, in populations of predominantly pre-menopausal women. Studies were required to report diagnostic histopathology data for at least 500 women. Relevant outcomes were the prevalence and incidence of EH, and/or the impact of pre-specified risk factors including age, body mass index (BMI) and diabetes mellitus. Results: In total, 3785 records were screened, and 31 references, describing 29 different studies, were included in the review. The incidence of EH among pre-menopausal women increased with age and was as high as 121 and 270 cases per 100, 000 woman-years in South Korean women aged 46–50 years and US women aged 45–49 years, respectively. The prevalence of EH was highly dependent on the population studied. Estimates of EH prevalence in 14 studies of pre-menopausal women with abnormal uterine bleeding (AUB) ranged from 3.4% to 265%, higher than the reported prevalence in two studies of women with infertility (0.9% and 3.0%). Studies of risk factors found increasing age, BMI and diabetes to be associated with an increased prevalence of EH. Conclusions: Published data on the epidemiology of EH in pre-menopausal women are heterogeneous, with considerable variation in study methodology and populations, and in how EH subtypes are reported. The main factors affecting the reported prevalence and incidence of EH are the reason a biopsy was performed – particularly whether patients had AUB, a key symptom associated with EH – and the presence of known risk factors.